AK2 Promotes the Migration and Invasion of Lung Adenocarcinoma by Activating TGF-β/Smad Pathway In vitro and In vivo - Cai, Fangfang; Xu, Huangru; Zha, Daolong; Wang, Xiaoyang; Li, Ping; Yu, Shihui; Yao, Yingying; Chang, Xiaoyao; Chen, Jia; Lu, Yanyan; Hua, Zi-Chun; Zhuang, Hongqin (Frontiers in Pharmacology, 2021)
Adenylate kinase 2 (AK2) is a wide-spread and highly conserved protein kinase whose main function is to catalyze the exchange of nucleotide phosphate groups. In this study, we showed that AK2 regulated tumor cell metastasis in lung adenocarcinoma. Positive expression of AK2 is related to lung adenocarcinoma progression and poor survival of patients. Knockdown or knockout of AK2 inhibited, while overexpression of AK2 promoted, human lung adenocarcinoma cell migration and invasion ability. Differential proteomics results showed that AK2 might be closely related to epithelial-mesenchymal transition (EMT). Further research indicated that AK2 regulated EMT occurrence through the Smad-dependent classical signaling pathways as measured by western blot and qPCR assays. Additionally, in vivo experiments showed that AK2-knockout in human lung tumor cells reduced their EMT-like features and formed fewer metastatic nodules both in liver and in lung tissues. In conclusion, we uncover a cancer metastasis-promoting role for AK2 and provide a rationale for targeting AK2 as a potential therapeutic approach for lung cancer.